Complications of Intramedullary Blocking Osteosynthesis of Bones of Limbs and Ways to Prevent Them - Mansyrov, A.B.; Lytovchenko, V.O.; Gariachyi, Ye.V. (TERRA ORTHOPAEDICA, 2020)
Summary. The main condition for preventing complications of intramedullary blocking osteosynthesis of long bones is following the tactical and technical principles of osteosynthesis and conscious rejection of such surgical techniques and manipulations that can lead to disturbances of the course of reparative processes of bone tissue. Objective. On the basis of the study and summary of the identified complications of intramedullary blocking osteosynthesis of diaphyseal fractures of bones of limbs, to determine ways to prevent complications of the reparation. Materials and Methods. The results of treatment of 403 patients who underwent intramedullary blocking osteosynthesis of the femur, tibia and humerus types A1-A3, B1–B3 and C2 by AO/ASIF were studied and analyzed. Results. Analyzing the technological complications that we have divided, depending on the consequences they led to, early (up to 2 weeks after surgery), late (2 weeks after surgery) and reparative, we found that the most common technological mistakes were incorrect preoperative planning and disruption of technology and surgery, which in 21.6% of cases led to instability of bone fragments in the fracture area, and the absence or disruption of recovery and rehabilitation of patients, which occurred in 26.3% of cases. Disorders of osteosynthesis technology, namely, significant intra-operative traumatization of bone fragments and soft tissues, and non-eliminated soft tissue interposition resulted in inappropriate consolidation of bone fragments in 39% and 13%, respectively. The main cause of reparative complications was bone marrow drilling, which was performed for 56% of the patients with delayed consolidation of bone fragments, 56.3% of the patients with false joints, and 48% of the patients with bone fractures. Conclusions. Strict following the tactical and technical principles of intramedullary blocking osteosynthesis and rejection of bone marrow drilling without indications will reduce the incidence of bone dysregeneration. The study of the effect of bone marrow drilling on reparative bone regeneration in intramedullary blocking osteosynthesis is actual and needs further deep analysis.